Interpreting neonatal hip sonography: intraobserver and interobserver variability. Issue 3 (May 2020) - Pedrotti, Luisella; Crivellari, Ilaria; Degrate, Alessandro; De Rosa, Federica; Ruggiero, Francesca; Mosconi, Mario
Abstract : The purpose of this study is to state the reliability of neonatal hip ultrasound interpretation, defining the intra and interoperator variability in the evaluation of the scans. We considered a sample of 2071 scans (coming from 798 patients who attended the screening programme for hip dysplasia), which were interpreted by the operator who obtained and read the images at the screening time and then by a different operator who saw the images for the first time. Both the intra and interoperator variability of α and β angles' values resulted statistically not significative (intraclass correlation coefficient > 0.8) and determining a class shift (according to the Graf's classification) in a nonstatistically significative number of cases (agreement percentage >91% and Cohen's κ >0.8). Hip sonography can reliably detect hip dysplasia and the intra and interoperator variability in the interpretation of the exam is NS when the examination is correctly executed.